Absorbable and tissue-adhesive full-bio-based hemostatic material and preparation method thereof
The microstructured dry gel prepared by cross-linking natural polyphenols and natural polymers solves the problems of insufficient rapid blood flow and storage stability of existing hemostatic materials, achieving rapid hemostasis and stable storage, and is suitable for the treatment of incompressible bleeding.
Patent Information
- Application Number
- CN202411566052.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-10
AI Technical Summary
Existing hemostatic materials are not effective at stopping bleeding under rapid pressure and lack storage stability and ease of use, making them ineffective in dealing with incompressible bleeding.
By using natural polyphenols and natural polymers to form a microstructured dry gel through ionic cross-linking, combined with strong electrostatic attraction and hydrogen bonding, an absorbable and tissue-adhesive all-biobased hemostatic material is prepared. It can rapidly absorb and coagulate whole blood and seal the bleeding site when a blood clot forms.
It achieves rapid hemostasis, enhanced blood removal capacity and storage stability, while avoiding secondary tissue damage, making it suitable for the treatment of incompressible bleeding under battlefield and clinical conditions.
Smart Images

Figure CN119280462A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hemostatic materials, and in particular, relates to an absorbable and tissue-adhesive fully bio-based hemostatic material and a preparation method thereof. Background Art
[0002] Massive bleeding caused by non-fatal trauma is one of the main causes of death and disability on the battlefield and in civilian accidents, and uncontrolled bleeding accounts for more than 30% of trauma deaths. Because massive blood loss can lead to symptoms such as hypothermia, coagulopathy, acidosis, sepsis, and organ failure. In this case, rapid and effective bleeding control is crucial. More than 50% of these deaths can be prevented if urgent and effective hemostasis measures are taken. Therefore, the development of advanced hemostasis products and technologies for pre-hospital bleeding control of the wounded to improve survival rates and reduce medical costs is an urgent resource on the battlefield and in accidents.
[0003] Despite the extensive research efforts that have been conducted, rapid pressurization of blood flow at the wound site remains a key challenge in the treatment of incompressible and massive bleeding. Existing local hemostats are primarily intended to enhance and accelerate intrinsic blood coagulation to achieve hemostasis, such as by concentrating coagulation factors through rapid water absorption, or by local delivery of procoagulants. However, due to the inherent progressiveness of blood clot formation, the common strategy of relying solely on hemostatic agents (such as thrombin and kaolin) to promote blood coagulation is limited by slow coagulation rates and coagulation disorders. The existing alternative strategy is to physically block the bleeding site through bioadhesive sealants, whose adhesion and sealing properties play a key role in hemostasis. However, due to their non-nanoporous structures, existing bioadhesives are slow and ineffective in rapidly pressurizing blood. Clinical and battlefield situations also have special requirements for ease of use and storage stability. Meeting these challenges requires the development of new designs and materials for incompressible bleeding.
[0004] In nature, some marine organisms have microporous structures and adhesive functions, such as mussel plaques with microporous structures and flatworms with glandular channels. A large number of studies have been inspired by mussels to prepare catechol-based adhesives. They can form moderate wet adhesion but cannot mimic the porous structure in vivo. These unstructured designs can avoid leakage and facilitate sealing, but in turn limit the ability to absorb and manipulate interfacial fluids. This limitation is unfavorable under bleeding conditions because rapidly pressurized blood can wash away hemostatic agents and destroy fragile blood clots. Even with dry matrices or hydrophobic repellents, unstructured bioadhesives cannot quickly remove interfacial fluids. Therefore, absorption and resistance to pressurized blood flow are crucial for hemostatic technologies to treat incompressible bleeding.
[0005] Inspired by microstructured adhesives in nature, we propose microstructured bioadhesive hemostatic materials (GTA) based on natural polyphenols to stop incompressible bleeding. This bioadhesive can rapidly absorb and coagulate whole blood while forming strong bioadhesion without compression to resist blood pressure and seal the bleeding site. They are formed by ionically crosslinking natural polyphenols in macroporous xerogels. Unlike existing unstructured bioadhesive hemostatic materials, hemostatic xerogels are tough, all-natural, biodegradable, and can promote blood coagulation. Their large pores can enhance rapid convection and effectively remove interfacial fluids, while the formation of blood clots can help block the pores within the gel to achieve sealing properties. The cross-linked functional natural polyphenols have universal adhesive properties and accelerate hemostasis. Compared with wet gels, xerogels are more storage stable and convenient to implement. And they can be gently removed after application without secondary damage to tissues. All results show that GTA has clinical translation ability and can provide effective treatment for potentially lethal incompressible bleeding and wound healing, and can work well in battlefield or clinical conditions. Summary of the invention
[0006] In order to overcome the problems existing in the prior art, the present invention provides an absorbable and tissue-adhesive fully bio-based hemostatic material and a preparation method thereof.
[0007] To achieve the above objectives, the present invention provides, in a first aspect, an absorbable and tissue-adhesive fully bio-based hemostatic material comprising the following components: a natural polymer, a natural polyphenol and deionized water.
[0008] Furthermore, the mass fraction of the natural polyphenols is 20.0% to 40.0% of the solid content in the hemostatic material.
[0009] Furthermore, the natural polyphenols are one or more of gallic acid, tannic acid, protocatechuic acid, and salvianolic acid A.
[0010] Furthermore, the natural polymer is one or more of gelatin, chitosan, collagen, and silk fibroin.
[0011] Furthermore, the ratio of the total mass of the mixture of the natural polymer and the natural polyphenol in the hemostatic material to water is: 50 g to 100 g of the mixture is added to every liter of water.
[0012] The second aspect of the present invention provides a method for preparing the above-mentioned hemostatic material, which comprises: dissolving a natural polymer and a natural polyphenol in deionized water to form a homogeneous solution, and performing vacuum freeze-drying after gel conversion to obtain the same.
[0013] Furthermore, in the gel conversion, the dissolution temperature is 40°C to 60°C, and the time is 0.5h to 2h; the gel temperature is 18°C to 25°C, and the time is 1h to 2h.
[0014] Furthermore, the vacuum freeze-drying conditions are: freezing in a -18°C to -25°C refrigerator for 10h to 14h and then vacuum freeze-drying at -30°C to -40°C.
[0015] The third aspect of the present invention provides a hemostatic material prepared by the above method.
[0016] Through the above technical solution, the present invention can at least achieve the following beneficial effects:
[0017] 1. The present invention combines natural polyphenols with natural polymers through ionic crosslinking, and obtains a microstructured bioadhesive hemostatic material (GTA) by vacuum freeze-drying after gel conversion. The GTA can quickly absorb and coagulate whole blood, and at the same time form a strong bioadhesion force. It can resist blood pressure and seal the bleeding site without any pre-treatment such as compression or photothermal curing.
[0018] 2. The present invention is different from existing non-structured bioadhesive hemostatic materials. Its large pores can enhance rapid convection and effectively remove interfacial fluids, and the formation of blood clots can help block the pores in the gel to achieve sealing properties. It is also all-natural and biodegradable.
[0019] 3. The present invention can provide strong mechanical strength through the strong electrostatic attraction and hydrogen bonding between the amino groups in the natural polymer and the carboxyl groups in the natural polyphenols, and can also provide strong tissue adhesion through rapid gelation of absorbed liquid and the catechol / pyrogallol in the structure, which helps to effectively fix on the wound surface during trauma treatment to achieve long-term hemostasis.
[0020] 4. Conventional hemostatic materials are usually wet and easily lose water during storage, which leads to failure. In addition, they often cause secondary damage during removal. The dry gel prepared by the present invention has better storage stability and convenient implementation. It can be gently removed after application without causing secondary damage to the tissue. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0022] Figure 1 This is the SEM image of the present invention;
[0023] Figure 2 is a coagulation performance diagram of the present invention;
[0024] Figure 3 This is a SEM image of blood cells after the coagulation test of the present invention;
[0025] Figure 4 This is a diagram of the wet tissue adhesion performance of the present invention;
[0026] Figure 5 This is a contact angle diagram of the present invention and whole blood;
[0027] Figure 6 This is a diagram of the cell compatibility of the present invention. DETAILED DESCRIPTION
[0028] Unless otherwise specified, the materials and reagents used in the present invention are commercially available.
[0029] Example 1
[0030] Preparation process of sample No. 1:
[0031] 1) Take 0.8 g of collagen, dissolve it in 10 mL of deionized water, and heat it to 50°C.
[0032] 2) Add 0.2 g of gallic acid to the solution and heat at 50°C for 1 h.
[0033] 3) Cool to 20°C and gel for 2 hours.
[0034] 4) Freeze at -20℃ for 12 hours, then take out and freeze-dry at -30℃.
[0035] Example 2
[0036] Preparation process of sample No. 2:
[0037] 1) Take 0.48 g of silk fibroin, dissolve it in 10 mL of deionized water, and heat it to 60°C.
[0038] 2) Add 0.32 g of tannic acid to the solution and heat at 60°C for 0.8 h.
[0039] 3) Cool to 23°C and gel for 1.5 hours.
[0040] 4) Freeze at -18℃ for 14h, then take out and freeze-dry at -35℃.
[0041] Example 3
[0042] Preparation process of sample No. 3:
[0043] 1) Take 0.63 g of gelatin, dissolve it in 10 mL of deionized water, and heat it to 55°C.
[0044] 2) Add 0.27 g of salvianolic acid A to the solution and heat at 55°C for 1.2 h.
[0045] 3) Cool to 19°C and gel for 1.6 hours.
[0046] 4) Freeze at -23℃ for 11h, then take out and freeze-dry at -38℃.
[0047] Example 4
[0048] Preparation process of sample No. 4:
[0049] 1) Take 0.375 g of chitosan, dissolve it in 10 mL of deionized water, and heat it to 45°C.
[0050] 2) Add 0.125 g of protocatechuic acid to the solution and heat at 45°C for 0.5 h.
[0051] 3) Cool to 25°C and gel for 1.8 hours.
[0052] 4) Freeze at -19℃ for 10 hours, then take out and freeze-dry at -32℃.
[0053] Control
[0054] The gel without adding natural polyphenols is numbered CK, and the processing process and quality are selected in accordance with the corresponding embodiment.
[0055] like Figure 1 , which are scanning electron microscope images of the samples of the embodiments, in which: (a) is embodiment 1; (b) is embodiment 2; (c) is embodiment 3; (d) is embodiment 4. The pores of the obtained hemostatic material are between 100-200 μm, which is consistent with the size of blood components, and is conducive to the entry of blood components such as red blood cells, so as to achieve the purpose of absorbing and aggregating blood components to form thrombi, and physically blocking and sealing wounds.
[0056] Figure 2 The sample of the embodiment and the gel number CK without adding natural polyphenols were used for comparison. The whole blood coagulation index (BCI) was used to evaluate the coagulation performance of the sample. CK and the sample of the embodiment were placed in a culture dish and 100 μL of whole blood was evenly added. In addition, 100 μL of whole blood was used as a blank control. After contacting with the blood for 15 minutes, 2 mL of deionized water was added to the culture dish without destroying the coagulated blood, and then incubated for 5 minutes at 37°C and 30 rpm. The color change of the water represents the degree of blood coagulation. Finally, 200 μL of the above solution was taken in a 96-well plate, and its absorbance was measured at 540 nm with an enzyme marker, and the color of the solution and the sample changes after coagulation were recorded by taking pictures. The results showed that compared with the blank group, CK and the sample of the embodiment had a certain coagulation phenomenon. In comparison, the whole blood in contact with the sample of the embodiment had completely coagulated into a blood clot. In order to quantitatively describe the hemostatic performance, the quantitative coagulation index (BCI) was calculated for the above test results. The lower the BCI value, the higher the coagulation rate. As can be seen from the figure, the coagulation value of the example sample is much lower than that of the CK group, indicating that its coagulation effect is better. The results show that the introduction of natural polyphenols can optimize the hemostatic effect of hemostatic materials.
[0057] Figure 3The example sample and the gel number CK without adding natural polyphenols were used for comparison. In order to study the interaction between red blood cells and CK and the example sample, the sample after the coagulation test was soaked in PBS containing 2.5w% glutaraldehyde at room temperature overnight to fix the red blood cells on the sample. Subsequently, the samples were soaked in a series of gradient anhydrous ethanol-PBS solutions (25%, 50%, 75%, 100%) for 15 minutes in turn for gradient dehydration. Finally, the sample was dried and the morphology of red blood cells on the sample surface was observed by scanning electron microscopy. As can be seen from the figure, the surfaces of CK and the example sample materials are covered with a large number of blood cells, both of which are easy to absorb and aggregate blood components. The blood components can enter the pores of the dry gel to form blood clots, and at the same time, physical blockages can be formed to seal the wound. In addition, the number of platelets on the gel of the example sample group is more and thicker, indicating that natural polyphenols are beneficial to activating platelets and further enhancing the hemostatic properties of the hemostatic material.
[0058] Figure 4 The samples of the examples and gel number CK without natural polyphenols were used for comparison. Different types of mechanical tests were performed to evaluate the wet tissue adhesion performance of the samples of the examples to measure the interface toughness (180 degree peel test, ASTM F2256) and shear strength (lap shear test, ASTM F2255). As can be seen from the figure, the samples of the examples showed strong adhesion to the pig skin stained with blood (such as the interface toughness of Example 1 was 230.28±21.24 J / m 2 , shear strength is 89.99±19.33 kPa), which is much better than the CK group. During use, the hemostatic material prepared by the present application has a high wet tissue adhesion performance.
[0059] Figure 5 The sample of the embodiment and the gel number CK without adding natural polyphenols were used for comparison. The sample was flattened and fixed on the surface of a metal plate, and a whole blood solution was dripped onto the surface of CK and the sample of the embodiment using a contact angle tester (HKCA-40) to measure the blood contact angle. According to the test results, both CK and the sample of the embodiment have good affinity for blood, and the contact angles are 52.96±3.64° and 46.82±0.33° (Example 1), respectively. In contrast, the addition of natural polyphenols optimizes the affinity of the hemostatic material for blood, because the phenolic hydroxyl groups in the structure of natural polyphenols are added.
[0060] Figure 6 The samples of the embodiment and gel number CK without natural polyphenols were used as controls. The samples were co-cultured with L929 cells at different extraction ratios for 24 hours. The test results showed that compared with CK, the samples of the embodiment maintained a better cell survival rate at the three extraction ratios, even at 1.50 and 1.00 cm 2 / mL extraction ratio, the cell survival rate is higher than that of the negative group, indicating that at a certain extraction ratio, the sample of the embodiment can promote cell growth. According to the recommendations of the International Organization for Standardization (ISO / EN 10993-5), a cell survival rate lower than 70% indicates that the test material has potential cytotoxicity, so the sample extract of the embodiment has low cytotoxicity to mammalian cells.
[0061] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A fully bio-based hemostatic material that is absorbable and tissue-adhesive, characterized in that: The invention comprises the following components: natural polymer, natural polyphenol and deionized water.
2. The absorbable and tissue-adhesive fully bio-based hemostatic material according to claim 1, characterized in that: The mass fraction of the natural polyphenols is 20.0% to 40.0% of the solid content in the hemostatic material.
3. The absorbable and tissue-adhesive fully bio-based hemostatic material according to claim 1, characterized in that: The natural polyphenols are one or more of gallic acid, tannic acid, protocatechuic acid and salvianolic acid A.
4. The absorbable and tissue-adhesive fully bio-based hemostatic material according to claim 1, characterized in that: The natural polymer is one or more of gelatin, chitosan, collagen, silk fibroin, sodium carboxymethyl cellulose and sodium alginate.
5. The absorbable and tissue-adhesive fully bio-based hemostatic material according to claim 1, characterized in that: The total mass ratio of the mixture of natural polymer and natural polyphenol in the hemostatic material in the aqueous solution is 50-100 g / L.
6. A method for preparing an absorbable and tissue-adhesive all-biobased hemostatic material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: dissolving natural polymer and natural polyphenol in deionized water to form a homogeneous solution, and performing vacuum freeze drying after gel conversion to obtain the homogeneous solution.
7. The absorbable and tissue-adhesive fully bio-based hemostatic material according to claim 6, characterized in that: In the gel conversion, the dissolution temperature is 40° C. to 60° C., and the time is 0.5 h to 2 h; the gel temperature is 18° C. to 25° C., and the time is 1 h to 2 h.
8. The absorbable and tissue-adhesive fully bio-based hemostatic material according to claim 6, characterized in that: The vacuum freeze drying conditions are: freezing in a -18°C to -25°C refrigerator for 10h to 14h and then vacuum freeze drying at -30°C to -40°C.
9. The hemostatic material prepared according to the method according to any one of claims 7-8.